PENERAPAN PENDEKATAN KONTEKSTUAL TERHADAP PENGUASAAN KONSEP DASAR MATERI VOLUME BENDA PUTAR - Alpha Galih Adirakasiwi; Attin Warmi; Adi Ihsan Imami (JPPM (Jurnal Penelitian dan Pembelajaran Matematika), 2018)
ABSTRACTThe purpose of this study was determine the application of contextual teaching learning approach to improve the mastery of concepts volume of the rotary object. The study design was nonequivalent pretest-posttest control group design. Data collection technique used pretest and posttest to determine the mastery of concepts of volume of the rotary object. Hypothesis testing using t-test to compare the the mastery of concepts volume of the rotary object in the experimental class and control class, then a further test by comparing the mean (compare means) and average absolute gain Based on the research result the data show that it can be concluded that the approach of contextual learning significantly distinction of concepts volume of the rotary object. Keywords:  Contextual Teaching Learning Approach, The Mastery of Concepts, Volume of The Rotary Object